(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Disease-Modifying Antirheumatic Drugs (DMARDs) play a vital role in the management of Rheumatoid Arthritis (RA). This update aims at focusing some important and novel aspects of biological DMARDs. Recent advances in biological therapy have opened a new window of opportunity for this potentially crippling disorder particularly patients refractory to conventional DMARDs. Close association of cytokine network in the pathophysiology of rheumatoid arthritis has facilitated the development of new biological agents and revolutionized the treatment. Novel drugs such as anti-tumor necrosis factor-alpha (anti-TNF-?) (eg, certolizumab), anti-interleukin-1 (anti-IL-1) (eg, anakinra), anti-interleukin-6 (antiIL-6) (eg, tocilizumab), T-cell depletor (eg, abatacept), anti-cluster differentiation 20 (anti-CD-20) (eg, rituximab) have recently joined with the existing biological therapy in the arena of RA. Emerging agents like adhesion molecule inhibitors, anti-interleukin-15 (anti-IL-15), fusion protein-cytotoxic T-lymphocyte-associated antigen 4-immunoglobulin G1 (CTLA4Ig) are also under investigations. Higher potency, quicker onset of action, less frequency of administration are the main advantages as opposed to potential serious side effects such as infection susceptibility, injection site reaction, Systemic Lupus Erythematosus-like (SLE-like) and Multiple Sclerosis-like (MS-like) symptoms and higher price. Combination of biologicals is not recommended because of higher rate of adverse events and lack of additive effects. But biological DMARDs in combination of Methotrexate (MTX) are now a preferred choice of many rheumatologists. The last but not the least option for aggressive and refractory patients of RA is biological DMARDs. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22933 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014